Republic of Tajikistan : Poverty Reduction Strategy Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
The Poverty Reduction Strategy (PRS) of the Republic of Tajikistan for 2010-12 aims to serve as a medium-term program for the implementation of the National Development Strategy up to 2015. It will determine the major socioeconomic development of the country during this period, taking into account the impact of the global economic and financial crisis. The PRS, taking into account available resources and additional needs, indicates concrete actions for implementing institutional and economic reforms.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet